2010
DOI: 10.1007/s11540-010-9172-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dormancy and Sprouting Behavior of CIP Elite and Advanced Clones Under Different Storage Conditions in Uzbekistan

Abstract: In potato breeding and selection, storability should be regarded as equally important as yield, disease resistance, and quality. A study documenting the dormancy period, sprouting behavior, and weight loss of 17 International Potato Center potato elite and advanced clones was carried out in Tashkent, Uzbekistan, under cellar and cold store conditions, during 2008 and 2009. Ninety tubers of each of 17 clones were allocated to experimental units of 30 tubers each placed in trays and randomized in three replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 5 publications
4
19
0
Order By: Relevance
“…It has been observed in previous studies that multiple sprouting cultivars show a slower growth rate of their longest sprout [52]. In the case of Exp-1, irrespective of the variety, the longest sprout resulted in being associated with the highest number of sprouts per tuber longer than 2 mm, thus consistent with Carli et al [38] that did not find any correlation between number of sprouts and length of the longest sprout. Moreover, as regards genotype, the longest sprout was recorded in Europa and Spunta in accordance with results of Carli et al who reported that clones with shorter dormancy often showed a greater length of their longest sprout [38].…”
Section: Exp-2supporting
confidence: 88%
See 2 more Smart Citations
“…It has been observed in previous studies that multiple sprouting cultivars show a slower growth rate of their longest sprout [52]. In the case of Exp-1, irrespective of the variety, the longest sprout resulted in being associated with the highest number of sprouts per tuber longer than 2 mm, thus consistent with Carli et al [38] that did not find any correlation between number of sprouts and length of the longest sprout. Moreover, as regards genotype, the longest sprout was recorded in Europa and Spunta in accordance with results of Carli et al who reported that clones with shorter dormancy often showed a greater length of their longest sprout [38].…”
Section: Exp-2supporting
confidence: 88%
“…In the case of Exp-1, irrespective of the variety, the longest sprout resulted in being associated with the highest number of sprouts per tuber longer than 2 mm, thus consistent with Carli et al [38] that did not find any correlation between number of sprouts and length of the longest sprout. Moreover, as regards genotype, the longest sprout was recorded in Europa and Spunta in accordance with results of Carli et al who reported that clones with shorter dormancy often showed a greater length of their longest sprout [38]. Principal component analysis confirmed in particular that sprouting characteristics such as number of sprouts longer than 2 mm, the length of the longest sprout, and sprouting activity, were as affected by dormancy class as by breaking-dormancy treatments, and that probably there was a synergistic effect between the combination short-, medium-dormant varieties and 20 • C + GA 3 (T5, T6 in Exp-1, and U-T4 in Exp-2) breaking-dormancy treatment.…”
Section: Exp-2supporting
confidence: 88%
See 1 more Smart Citation
“…Premature sprouting is one of the major causes of loss during postharvest storage of potato tubers [3, 4]. The sprouting behavior of potato tubers depends mainly on the plant genotype [5, 6], but it is also influenced by storage conditions, the type of field soil or environmental factors such as weather during growth [7, 8]. For example, tubers of the same potato variety grown in different fields often show differences in storage stability (personal communication with Austrian potato producers).…”
Section: Introductionmentioning
confidence: 99%
“…Also, since the sprout depends on the tuber materials for growth, if there are several sprouts on the tuber, an inter-sprout competition for growth factors will be imposed by the size of the tuber. With fairly large tubers, no effect of size will be noticeable, but with decreasing size, as size is smaller, growth of sprouts will be lesser (Carli & Mihovilovich, 2010). In this research, tuber sizes used for experimentation were very small i.e.…”
Section: Loss Due To Sproutmentioning
confidence: 80%